Rumah Berkarya Pelajar: Manifestation of the IPM Movement Strategy in the New Era - Syifa Yustiana , Daei Aljanni, (Indonesian Journal of Muhammadiyah Studies (IJMUS), 2025)
Rumah Berkarya Pelajar is the vision of IPM Central Java which is oriented towards the sustainability of the cadre movement and the strengthening of an active and progressive student ecosystem. This concept was born as a continuation of the previous movement model, with a more adaptive and systematic approach to the challenges of the times. This study uses descriptive and comparative methods to explain the main elements of the Rumah Berkarya Pelajar and compare it with the pattern of previous student movements. The 9 Priority Pyramid is the main foundation in building cadre capacity, while the two main strategies, namely Gayeng Students and the Gayeng Student Network, are the driving force. Gayeng Students present an exciting, inclusive, and sustainable action agenda, while the Gayeng Student Network is the result of this sustainability, forming a community of cadres that continues to grow and network widely. The results of the study show that Rumah Berkarya Pelajar is not only an innovation, but also a long-term strategy in creating cadres who are empowered, networked, and able to answer the challenges of the times. In conclusion, this concept presents a movement model that is more dynamic, collaborative, and has a wide impact on the student ecosystem